Genie Business - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet likens the fascination of painting furniture to the magic of a genie. Describes tips and tricks for painting furniture. Includes small stylized illustrations throughout and decorated covers. The advertisement features a racially-stereotyped depiction of a genie, the anglicized jinn derived from Islamic mythology. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Jinn; Furniture painting; Stereotypes (Social psychology)